Pauvreté, décentralisation et changement social. Éléments pour la reconstruction d’une société politique - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Pauvreté, décentralisation et changement social. Éléments pour la reconstruction d’une société politique